Jovens rurais no sertão sergipano : escolarização e identidades culturais - Menezes, Isabela Gonçalves de (2012)
This dissertation is the result of a comprehensive and qualitative research aimed to investigate issues related to the cultural identities of young people, sons of smallholders and agrarian reform settlers, who live on the rural hinterland of Sergipe. They are aged between 14 and 29 years and they are studying at regular urban high schools. The sample was composed of 194 rural youngs who were investigated through a questionnaire. From the data analysis, it was discovered that the majority of the rural youth have age-grade discrepancy and have been failed at least once. However their parents recognize the importance of sending children to school, especially as a way to ensure their future. They like to go to school to learn and to socialize, feeling comfortable in this space. When they go to the city to continue studying, they fell like if they change , say some reports. Although their relatives approving their studies, most of the young studied faces difficulties in school life. Because they are in high school, they differ from those who have not studied and use the rural language and most part of them communicates in one way at home and in another way at school. For their own future, even liking rural areas, they want to live in the city and do not want to reproduce the social status of family farmers. They want a better future and a job that gives them financial independence, however, it was observed a relationship between the few young people who want to stay on the field and dairy farming. They are sons of small farmers who have dairy cattle who want to stay on the rural area and take care of the family s property. It can be concluded that the rural young people build their own identities in urban high school, while deconstruct some aspects of their rural identities, to reconstruct them, in a new context and situation, especially on individualization and on perspective of continue studying and graduate in a university, aiming for personal achievement and social fitting.